Efektivitas aplikasi game edukasi wordwall puzzle terintegrasi budaya lokal ngada "ngadhu-bhaga" untuk meningkatkan kemampuan bahasa anak usia dini - Mere, Veronika Owa; Fono, Yasinta Maria; Ngura, Elisabet Tantiana; Laksana, Dek Ngurah Laba (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2026)
This study evaluates the effectiveness of the Wordwall Puzzle educational game application, integrated with Ngada local culture "Ngadhu-Bhaga," in improving early childhood language skills. Low language proficiency observed at TKN Bobou necessitated this intervention. Using a quantitative approach with a one-group pretest-posttest design, 13 children aged 5–6 years (Group B) were selected via purposive sampling. Data were collected through observation, interviews, and language tests, then analyzed using a Paired Sample t-test. Results indicated a significant improvement in language skills, with the mean score increasing from 10.15 in the pretest to 13.85 in the posttest. Statistical analysis revealed a t-value of -8.056 and a p-value of < .001, indicating significant differences after the intervention. Cohen’s d analysis showed a very large effect size, suggesting that digital media relevant to a child's cultural environment effectively stimulates receptive and expressive language. The integration of local culture serves as a cognitive bridge, making learning more meaningful and contextual.